Some physical fitness and physiologic factors in overweight diabetic and nondiabetic elderly women - Vahid Valipour Dehnou; Azam Darvishi; Parvaneh Alinezhad; Hadis Mehrabi Fard (Mashhad University of Medical Sciences, 2021)
Introduction: Diabetes interfere the glucose homeostasis and reduces physical fitness and brain health. This study was performed with aim to compare some physical fitness and physiologic factors in overweight diabetic and non-diabetic elderly women. Methods: This descriptive-analytical study was performed on 34 elderly women in Khorramabad city in 2019. One week before performing physical fitness tests, blood sample was taken in fasting state to measure serum levels of glucose, irisin, HbA1c and BDNF. Five days before doing the study, the subjects were familiarized with the method of performing the tests. Then, on the day of the study, some physical fitness tests special for the elderly were performed. Data were analyzed by Independent t-test and Pearson correlation coefficient test. P< 0.05 was considered statistically significant. Results: There was no significant difference between the diabetic and non-diabetic groups in all physical fitness variables (p>0.05). However, all physiologic variables showed a significant difference (p<0.05). Also, in the non-diabetic group, there was a significant negative correlation between BDNF and HbA1c (p = 0.0005 and r = -0.824) and irisin and HbA1c (p = 0.0005 and r = -0.734) and a significant positive correlation between BDNF and irisin (p = 0.004 and r = 0.608). But in the diabetic group, there was a significant positive correlation between glucose and HbA1c (p =0.028 and r =0.586) and irisin and BDNF (p = 0.0005 and r = 0.853) and a significant negative correlation between glucose and irisin (P = 0.015 and r = -0.636), BDNF and HbA1c (p = 0.002 and r = -0.759) and irisin and HbA1c (p = 0.002 and r = -0.752). Conclusion: It seems that the level of physical fitness of overweight non-diabetic and diabetic elderly women is the same. But the non-diabetic group was better in physiological variables. Also, irisin plays more important role than BDNF in diabetes.